2014
DOI: 10.1123/jsr.2013-0044
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Physical Activity and Sports Participation After Autologous Cartilage Implantation: A Systematic Review

Abstract: Context:The assessment of physical activity and return to sport and exercise activities is an important component in the overall evaluation of outcome after autologous cartilage implantation (ACI). Objective: To identify the patient-report instruments that are commonly used in the evaluation of physical activity and return to sport after ACI and provide a critical analysis of these instruments from a rehabilitative perspective. Evidence Acquisition: A computerized search was performed in January 2013 and repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…The validated instruments fail in the assessment of frequency, intensity, and duration of sports participation. 48 We therefore asked patients specifically about their sporting routines including the abovementioned factors of sporting activity. In our study, we found that 82.9% of the patients still played sports regularly at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The validated instruments fail in the assessment of frequency, intensity, and duration of sports participation. 48 We therefore asked patients specifically about their sporting routines including the abovementioned factors of sporting activity. In our study, we found that 82.9% of the patients still played sports regularly at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In today’s literature, several studies can be found that analyze return-to-sports rates in ACI patients. 8,17,30 Return to work after ACI, however, appears to be of much less interest. Specific data describing duration of absence from work after ACI, ability to perform work at the same level as preoperatively, or simply grade of satisfaction at patients’ workplace after ACI are currently elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies presented patients’ general return-to-sport rates. 17,30 Detailed information regarding individual sporting activities, together with frequency and intensity of sports after ACI, is not yet found in today’s literature. We believe that this information is both relevant for the active ACI population as well as for the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies reported data on return to work after ACI 1,17,24 in the general population in contrast to the relatively large number of studies on return to sports after ACI. 19,28 The present review found that the surgical techniques of first-and second-generation ACI provide similar results in return to work. Return to work after surgical intervention with ACI is faster than return to sport (3.34 ± 2.75 vs 18 ± 4 months, respectively).…”
Section: Discussionmentioning
confidence: 54%